A polyethylene resin composition for weather-resistant mulch film, and a method of preparing and using the same
Patent Information
- Application Number
- CN202510553254.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0051]本发明的LLDPE树脂组合物所生产的地膜具有较高的横/纵向的拉伸负荷和较高的断裂标称应变。采用该树脂组合物生产的地膜具有较好的耐候性,覆地使用后,其机械性能保留率高,老化后依然具有较高的横/纵向的拉伸负荷和较高的断裂标称应变,能够满足地膜的回收和再利用,既解决地膜造成白色污染问题,又实现回收地膜的再利用。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a polyolefin mulch film material, and more specifically to a polyethylene resin composition for weather-resistant mulch film, its preparation method, and its application. Background Technology
[0002] Polyethylene blown agricultural ground cover film, or mulch film for short, has functions such as moisture retention, temperature increase, water conservation, and prevention of pests and diseases. It promotes plant growth and makes important contributions to increasing agricultural production and farmers' income. It has become an indispensable production material for agricultural production.
[0003] Data from the National Bureau of Statistics shows that in 2016, the area covered by plastic film in my country exceeded 275 million mu (approximately 18.3 million hectares), with a usage of 1.47 million tons. It is predicted that by 2024, the area covered by plastic film will reach 330 million mu (approximately 22.7 million hectares), with usage exceeding 2 million tons. Such large-scale use of plastic film has both advantages and disadvantages. On the one hand, it has played a significant role in improving the quality and efficiency of agriculture; on the other hand, it causes serious pollution to the soil and environment. Specifically, discarded plastic film fragments gradually cause irreversible soil deterioration, affecting permeability, reducing water content, weakening drought resistance, and causing secondary salinization. Furthermore, the residual film left in fields also causes "white pollution," impacting the environment.
[0004] The key to solving the problem of plastic film pollution is to achieve plastic film recycling, especially efficient and low-cost mechanical recycling. In 2014, the Xinjiang Uygur Autonomous Region Quality and Technical Supervision Bureau, considering the climate characteristics of Xinjiang, formulated DB / T 3189-2014 to replace the old standard with "recyclability" as the goal. In 2017, the Ministry of Agriculture and Rural Affairs launched an agricultural film recycling campaign and issued the mandatory national standard GB 13735-2017 "Polyethylene Blown Agricultural Ground Cover Film". The new local and national standards have improved the minimum nominal thickness, mechanical properties, and weather resistance of plastic film.
[0005] In the existing technology, in order to meet the requirements for plastic film recycling and to meet national / local standards, plastic film manufacturers in Xinjiang or those supplying plastic film to Xinjiang generally use compounding materials, which combine various polyethylene raw materials and additives to improve the stability of the blown film process and enhance the physical and mechanical properties and weather resistance of the plastic film.
[0006] However, this often leads to increased costs and more complex production processes for mulch film, resulting in inconsistent product quality. Therefore, there is an urgent need to develop a resin composition for use by mulch film manufacturers.
[0007] Light stabilizers are typically used to modify the matrix to improve the strength of the mulch film after use, thereby increasing its recyclability. However, simply adding solid hindered amine light stabilizers can lead to a loss of some of the material's mechanical properties. Summary of the Invention
[0008] To address the technical problems existing in the prior art, the purpose of this invention is to provide a weather-resistant polyethylene resin composition for mulch film, its preparation method, and its application. Mulch film produced using the weather-resistant polyethylene resin composition of this invention has high tensile load and nominal strain at break, and a high retention rate of physical and mechanical properties after artificial climate aging and actual use, effectively ensuring the mechanical properties during mulch film recycling. It can be widely used for the mechanical recycling of mulch film and improve the mulch film recycling rate.
[0009] A first aspect of the present invention is to provide a linear low-density polyethylene resin composition comprising LLDPE resin, an antioxidant, an opening agent, a compounding agent, optionally a nucleating agent, and optionally a solid hindered amine light stabilizer, wherein the compounding agent comprises a liquid light stabilizer and crosslinked rubber particles, the liquid light stabilizer being loaded on the surface of the crosslinked rubber particles.
[0010] The linear low-density polyethylene resin composition of the present invention contains linear low-density polyethylene resin (LLDPE) and additives such as antioxidants and opening agents. The resin composition also includes a composite additive formed by combining a liquid light stabilizer with cross-linked rubber particles. The addition of the composite light stabilizer can significantly improve the transverse / longitudinal tensile load of the polyethylene composition after aging, improve the stability of the mulch film product, simplify production, and improve performance.
[0011] According to the present invention, preferably, the crosslinked rubber particles are selected from at least one of the following rubber particles having a crosslinked structure: styrene-butadiene rubber particles, carboxylated styrene-butadiene rubber particles, natural rubber particles, acrylate rubber particles, ethylene-vinyl acetate copolymer particles, isoprene rubber particles, and acrylate-butadiene particles; more preferably, they are selected from at least one of styrene-butadiene rubber particles, carboxylated styrene-butadiene rubber particles, and ethylene-vinyl acetate copolymer particles; more preferably, the rubber particles are selected from crosslinked ethylene-vinyl acetate.
[0012] According to the present invention, preferably, the gel content in the crosslinked rubber particles is 60 wt% or higher.
[0013] According to the present invention, preferably, the crosslinked rubber particles are secondary particles composed of primary particles, the primary particles having an average particle size of 0.1-1 micrometer, preferably 0.1-0.5 micrometers, and the secondary particles having an average particle size of 10-60 micrometers, preferably 20-40 micrometers.
[0014] According to the present invention, preferably, the liquid light stabilizer is a liquid hindered amine light stabilizer, more preferably at least one of HS-765, HS-508, and HS-112 from Beijing Tiangang Additives Co., Ltd.
[0015] According to the present invention, preferably, the composite additive is a composite additive formed by loading a liquid light stabilizer onto the surface of spherical or nearly spherical cross-linked rubber particles.
[0016] According to the present invention, preferably, the preparation method of the composite additive includes: mixing an irradiated crosslinked rubber latex with a liquid light stabilizer, and spray drying it to prepare a powdered composite additive.
[0017] According to the present invention, preferably, the weight ratio of the liquid light stabilizer to the rubber latex based on solid content is (5-15):100, that is, in the preparation process of the composite additive, the weight percentage of the liquid light stabilizer is 5-15 wt% of the solid content of the rubber latex.
[0018] According to the present invention, preferably, the rubber latex raw material includes at least one of the following: styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, natural rubber latex, acrylate rubber latex, ethylene-vinyl acetate copolymer latex, isoprene rubber latex, and acrylic-butadiene latex, preferably styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, and ethylene-vinyl acetate copolymer latex, and more preferably ethylene-vinyl acetate copolymer latex.
[0019] The composite additive of the present invention, containing a liquid light stabilizer and crosslinked rubber particles, preferably uses the liquid light stabilizer of the present invention, a preferred ratio of light stabilizer to rubber particles of the present invention, and is prepared using the method for preparing fully vulcanized powdered rubber disclosed in Chinese patent application CN99125530.5. The difference is that the irradiated crosslinked rubber latex is first mixed with the liquid light stabilizer, and then spray-dried while stirring to prepare the composite powder. The rubber latex raw materials used in the present invention include at least one of the following: styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, natural rubber latex, acrylate rubber latex, ethylene-vinyl acetate copolymer latex, isoprene rubber latex, and acrylic-butadiene latex, preferably styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, and ethylene-vinyl acetate copolymer latex. The present invention uses common dispersion equipment (such as high-shear dispersing emulsifiers, colloid mills, etc.) to ensure that the powdered rubber particles and liquid light stabilizer are uniformly dispersed in water. After spray drying, the liquid light stabilizer fully covers the surface of the powdered rubber. Using the above method, the obtained composite additive has the following characteristics: the gel content in the cross-linked rubber particles is 60 wt% or higher; the cross-linked rubber particles are secondary particles composed of primary particles, the average particle size of the primary particles is 0.1-1 micrometer, preferably 0.1-0.5 micrometers, and the average particle size of the secondary particles is 10-60 micrometers, preferably 20-40 micrometers.
[0020] The LLDPE resin involved in this invention refers to a resin produced by copolymerization of ethylene and α-olefins such as butene-1, hexene-1, or octene-1 under certain temperature and pressure conditions. Preferably, the melt flow rate (at 190±5℃ and a load of 2.16 kg) (i.e., melt index) is ≤10 g / 10 min, more preferably ≤4 g / 10 min, and most preferably ≤2.5 g / 10 min. Preferably, the LLDPE resin is copolymerized from ethylene and α-olefins, wherein the α-olefin is preferably selected from at least one of butene-1, hexene-1, and octene-1; and / or, preferably, at 190±5℃ and a load of 2.16 kg, the melt flow rate of the LLDPE resin is ≤10 g / 10 min, more preferably ≤4 g / 10 min, and more preferably ≤2.5 g / 10 min.
[0021] The polyethylene composition of this invention, in addition to containing a composite additive comprising a liquid light stabilizer / crosslinked powdered rubber particles, preferably also includes a solid hindered amine light stabilizer. According to this invention, preferably, the solid hindered amine light stabilizer is selected from at least one of light stabilizer 770, light stabilizer 944, light stabilizer 622, and light stabilizer 3346. As mentioned above, simply adding a solid hindered amine light stabilizer to a polyethylene composition will result in a loss of some of the material's mechanical properties. In this preferred embodiment, combined with the composite additive of this invention, the composite additive and the solid hindered amine light stabilizer work synergistically, resulting in a polyethylene composition with higher tensile load and nominal strain at break. Even after aging, the tensile load and nominal strain at break remain high, better ensuring the mechanical properties during the recycling of the mulch film.
[0022] The polyethylene composition of the present invention, in addition to containing a composite additive comprising a liquid light stabilizer / crosslinked powdered rubber particles, further preferably includes a solid hindered amine light stabilizer and a nucleating agent.
[0023] According to the present invention, preferably, the nucleating agent is selected from at least one of organic nucleating agents and inorganic nucleating agents, more preferably from at least one of organic carboxylic acid nucleating agents, organic carboxylate nucleating agents, and organic phosphate nucleating agents, and more preferably from at least one of nucleating agent NA11, nucleating agent NA21, and nucleating agent 20E. In this preferred embodiment, combined with the composite additive of the present invention, the composite additive, solid hindered amine light stabilizer, and nucleating agent work synergistically to obtain a polyethylene composition with higher tensile load and nominal strain at break. After aging, the tensile load retention rate and nominal strain at break are further improved, which can further better guarantee the mechanical properties during the recycling of the mulch film.
[0024] According to the present invention, preferably, the antioxidant comprises a primary antioxidant and a secondary antioxidant; the primary antioxidant is hindered phenols, for example, including pentaerythritol [β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (antioxidant 1330), 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid (antioxidant 3114), β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate isooctyl ester (antioxidant 1135), and 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3 At least one of 5-triazine-2,4,6-(1H,3H,5H)-trione (antioxidant 1790); co-antioxidants include phosphites and thioesters, phosphites including, for example, tris(nonylphenyl) phosphite (TNPP), tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), bis(octadecyl) pentaerythritol diphosphite (antioxidant 618), pentaerythritol bis(2,4-tert-butylphenyl) diphosphite (antioxidant 626), bis(2,6-di-tert-butyl-4-tolyl) pentaerythritol phosphite (PEP-36), tetrakis(2,4-di-tert-butyloctaalkoxy-4,4'-biphenyl) phosphate, 2,2-ethylidene bis(4,6-di-tert-butylphenyl) fluorophosphite (antioxidant 398), etc.
[0025] According to the present invention, more preferably, the main antioxidant is a hindered phenolic antioxidant, preferably selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1330, antioxidant 3114, antioxidant 1135, and antioxidant 1790;
[0026] And / or, preferably, the auxiliary antioxidant is selected from at least one of phosphite antioxidants and thioester antioxidants, more preferably from at least one of phosphite antioxidants; even more preferably,
[0027] Phosphite antioxidants are selected from at least one of antioxidant TNPP, antioxidant 168, antioxidant 618, antioxidant 626, antioxidant PEP-36, tetrakis(2,4-di-tert-butyloctaalkoxy-4,4'-biphenyl) phosphate, and antioxidant 398.
[0028] According to the present invention, preferably, the antioxidant includes a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is a hindered phenolic antioxidant, and the secondary antioxidant is selected from phosphite antioxidants. Based on parts by weight, relative to 1000 parts of LLDPE resin, the content of the hindered phenolic antioxidant is 0.3-3 parts, preferably 0.3-2 parts, more preferably 0.5-1 parts; and the content of the phosphite antioxidant is 0.3-3 parts, preferably 0.3-2 parts.
[0029] According to the present invention, preferably, the content of the opening agent is 1-10 parts by weight, more preferably 1-5 parts, relative to 1000 parts of LLDPE resin.
[0030] According to the present invention, preferably, the opening agent is selected from at least one of inorganic opening agents and organic opening agents; the inorganic opening agent includes talc, diatomaceous earth, silica, etc., and the organic opening agent includes oleamide, erucamide, etc.
[0031] Preferably, the inorganic opening agent is selected from at least one of talc, diatomaceous earth, and silica.
[0032] Preferably, the organic opening agent is selected from at least one of oleamide and erucamide.
[0033] According to the present invention, preferably, based on parts by weight, the content of composite additives in the linear low-density polyethylene resin composition is 0.3-2 parts relative to 1000 parts of LLDPE resin; the content of solid hindered amine light stabilizer is 0-2 parts, preferably 0.3-2 parts; and the content of nucleating agent is 0-1.5 parts, preferably 0.3-1.5 parts, more preferably 0.5-1.2 parts.
[0034] According to the present invention, preferably, the weight ratio of liquid light stabilizer to crosslinked rubber particles in the composite additive is (5-15):100.
[0035] According to the present invention, preferably, based on parts by weight, the content of composite additives in the linear low-density polyethylene resin composition is 0.3-2 parts relative to 1000 parts of LLDPE resin; the content of solid hindered amine light stabilizer is 0.3-2 parts; and the content of nucleating agent is 0.3-1.5 parts.
[0036] According to the present invention, more preferably, based on parts by weight, the content of composite additives in the linear low-density polyethylene resin composition is 0.3-2 parts relative to 1000 parts of LLDPE resin; the content of solid hindered amine light stabilizer is 0.3-2 parts; and the content of nucleating agent is 0.3-1.5 parts, more preferably 0.5-1.2 parts.
[0037] According to the present invention, preferably, the weight ratio of liquid light stabilizer to crosslinked rubber particles in the composite additive is (5-15):100.
[0038] The additives described in this invention may also include commonly used additives in plastic processing, such as antistatic agents and acid absorbers, and their dosages are all conventional dosages, or may be adjusted according to actual requirements.
[0039] A second aspect of the present invention is to provide a method for preparing the linear low-density polyethylene resin composition described in the first aspect, comprising melt-blending raw materials including the LLDPE resin, antioxidant, opening agent, composite additive, optional nucleating agent, and optional solid hindered amine light stabilizer to obtain the linear low-density polyethylene resin composition.
[0040] Preferably, the method for preparing the linear low-density polyethylene resin composition includes the following steps:
[0041] Step 1: Premix the raw materials including the LLDPE resin, antioxidant, opening agent, composite additive, optional nucleating agent, and optional solid hindered amine light stabilizer; or, prepare an additive composition from the additive raw materials including the antioxidant, opening agent, composite additive, optional nucleating agent, and optional solid hindered amine light stabilizer, and then premix the additive composition with the LLDPE resin.
[0042] Step 2: The premixed mixture obtained in Step 1 is melt-blended to obtain the linear low-density polyethylene resin composition.
[0043] During the preparation process, the blending temperature of the materials corresponds to the typical processing temperature of the LLDPE matrix resin, and should be selected within a range that ensures complete melting of the matrix resin without causing its decomposition. Furthermore, depending on processing requirements, appropriate amounts of conventional plastic processing additives can be added to the blended materials. During the blending process, the components can be simultaneously added to a melt blending device via metering or other methods for melt blending; alternatively, the components can be pre-mixed uniformly using general-purpose mixing equipment, and then melt-blended and extruded in a rubber-plastic blending device to obtain the modified resin composition.
[0044] The conditions for the initial mixing and melt blending processes of the linear low-density polyethylene resin composition in this invention include, but are not limited to, the preparation conditions in the examples.
[0045] The rubber-plastic blending equipment used in the preparation method of this invention can be an open mill, internal mixer, single-screw extruder, twin-screw extruder, torque rheometer, or twin-rotor extruder, etc. The material mixing equipment is selected from commonly used mechanical mixing equipment in the art, such as high-speed mixers and kneaders.
[0046] A third aspect of the present invention is to provide a polyethylene film, wherein the polyethylene film is made of the linear low-density polyethylene resin composition described above or the linear low-density polyethylene resin composition prepared by the preparation method described above.
[0047] Preferably, the polyethylene film is obtained by blow molding, and more preferably, the blow-up ratio is >2.5.
[0048] A fourth aspect of the present invention is to provide a method for preparing the polyethylene film described in the third aspect, comprising the step of blow molding the linear low-density polyethylene resin composition described in the first aspect or the linear low-density polyethylene resin composition obtained by the preparation method described in the second aspect, preferably with a blow-up ratio > 2.5.
[0049] The fifth aspect of the invention is to provide the application of the linear low-density polyethylene resin composition described in the first aspect or the linear low-density polyethylene resin composition prepared by the preparation method described in the second aspect, or the polyethylene film described in the third aspect or the polyethylene film prepared by the preparation method described in the fourth aspect, in mulch film.
[0050] Compared with the prior art, the advantages of the present invention are:
[0051] The mulch film produced by the LLDPE resin composition of the present invention has high transverse / longitudinal tensile load and high nominal strain at break. The mulch film produced using this resin composition has good weather resistance, and after mulching, its mechanical properties are well retained. Even after aging, it still has high transverse / longitudinal tensile load and high nominal strain at break, which can meet the requirements for recycling and reuse of mulch film, thus solving the problem of white pollution caused by mulch film and realizing the reuse of recycled mulch film.
[0052] The polyethylene composition involved in this invention uses a composite additive containing a liquid light stabilizer and cross-linked rubber particles. The composite additive is formed by loading the liquid light stabilizer onto the surface of the cross-linked rubber particles. The cross-linked rubber particles in the composite additive are beneficial for the dispersion of the liquid light stabilizer, for absorbing free radicals, for reducing the migration of the liquid light stabilizer in the matrix, and for improving the mechanical properties (tensile load and nominal strain at break) of the polyethylene composition.
[0053] In a preferred embodiment of the present invention, the composite additive is used together with the solid hindered amine light stabilizer to produce a synergistic effect, which can effectively exert the function of the light stabilizer and improve the aging resistance of the resin. In a more preferred embodiment of the present invention, the composite additive is used together with the solid hindered amine light stabilizer and the nucleating agent to produce a synergistic effect to further improve the crystallization performance of the resin and also improve the blown film stability.
[0054] The polyethylene composition of the present invention has high transverse / longitudinal tensile load and high nominal strain at break. Moreover, it also improves the transverse / longitudinal tensile load and nominal strain at break of the aged film, and improves the blown film stability of the resin composition. In particular, when producing films with high blow-up ratio (>2.5), it significantly improves the stability of the film bubble, making the production simpler and more efficient. Detailed Implementation
[0055] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0056] The present invention is further described below with reference to embodiments. The scope of the claims is not limited to these embodiments, but is set forth in the appended claims.
[0057] The experimental data in this embodiment were measured using the following instruments and methods:
[0058] The test specimens for tensile load and nominal strain at break were tested in accordance with the national standard GB / T1040.3-2006 and the local standard of Xinjiang Uygur Autonomous Region DB65 3189-2014. The specimens were type 2, with a width of 10 mm, an initial mark distance of 50 mm between the fixtures, a test speed (no load) of 500 mm / min, and were stretched until the specimen broke. The maximum tensile load was measured to an accuracy of 0.01 N.
[0059] Artificial climate aging tests were conducted in accordance with GB / T 9345.1-2008 and Xinjiang Uygur Autonomous Region local standard DB653189-2014. Specific ultraviolet aging conditions were as follows: Type II lamps (UV-A340) were used, with a wavelength of 340 nm and an irradiance of 0.76 W / m². 2 •nm, illumination temperature 60℃, radiation time 4h (bright); condensation temperature 50℃, condensation time 4h (dark), alternating cycles for 240 hours.
[0060] HS-765 is the HS-765 liquid light stabilizer produced by Beijing Tiangang Additives Co., Ltd.
[0061] HS508 is the HS-508 liquid light stabilizer produced by Beijing Tiangang Additives Co., Ltd.
[0062] The nucleating agent HPN20E was purchased from Milliken.
[0063] The liquid light stabilizer / rubber particle composite of this invention is prepared using the method for preparing fully vulcanized powdered rubber disclosed in Chinese patent application CN99125530.5. The difference lies in that the irradiated crosslinked rubber latex is first mixed with the liquid light stabilizer, and then spray-dried while stirring to prepare the composite powder. The styrene-butadiene rubber latex is sourced from Yanshan Petrochemical High-Tech Co., Ltd.; the ethylene-ethyl acetate rubber latex is also sourced from Yanshan Petrochemical High-Tech Co., Ltd. Specific formulations are detailed in the preparation examples.
[0064] Preparation Example 1
[0065] Preparation method of composite additive with HS-765 / powdered styrene-butadiene rubber mass ratio of 1:5:
[0066] Take 8.6g of HS-765 liquid light stabilizer and 100g of irradiated crosslinked powdered styrene-butadiene rubber emulsion (solid content of 43%), mix them evenly, and then spray dry to prepare a composite additive with a mass ratio of HS-765 / powdered styrene-butadiene rubber of 1:5.
[0067] Preparation Example 2
[0068] Preparation method of composite additive of HS508 and ethylene-ethyl acetate rubber in a weight ratio of 1:10:
[0069] Take 5.4g of HS508 liquid light stabilizer and mix it with 100g of irradiated crosslinked ethylene-ethyl acetate rubber latex (solid content is 54%). Mix them evenly and then spray dry to prepare a composite additive with a mass ratio of HS-765 / powdered styrene-butadiene rubber of 1:10.
[0070] Example 1
[0071] Linear low-density polyethylene resin compositions were prepared using the following method (formulations are shown in Table 1, and the units of raw material usage in Table 1 are in g):
[0072] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min (test conditions: 190±5℃, load 2.16 kg), density: 0.918 g / cm³). 32000.0 g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0 g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 1.2 g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), and 6 g of composite additives with a mass ratio of HS-765 / powdered styrene-butadiene rubber of 1:5 (i.e., the composite additives prepared in Preparation Example 1) were obtained by twin-screw melt blending and granulation to obtain a linear low-density polyethylene resin composition. The initial mixing and melt blending process of the materials is as follows: First, all materials are weighed according to the proportion and initially mixed in a high-speed mixer for 20 seconds. Then, a twin-screw extruder (Coperon (Nanjing) Machinery Co., Ltd., length-to-diameter ratio 30:1, screw diameter 30 mm) is used for melt blending and granulation. The speed is 200 r / min, and the temperature is set to 170℃, 180℃, 190℃, 200℃, 200℃, and 200℃, with a feed rate of 14. The resulting granules are placed in a tray and treated in a 70℃ oven for 4 hours to remove moisture.
[0073] Plastic film blow molding process:
[0074] The linear low-density polyethylene resin composition obtained in this embodiment was used to prepare mulch film using a single-layer blow molding method. The blow molding machine was a German company, Kölin. The temperature settings of the blow molding machine were as follows: the temperature of each section was set to 160℃, 180℃, 200℃, 210℃, 210℃, 210℃, and 210℃. The screw speed was 55 r / min, the blown film width was 31 cm, the nominal thickness was 10 μm, and the blow-up ratio was 2.9.
[0075] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0076] Example 2:
[0077] The linear low-density polyethylene resin composition was prepared using the following method:
[0078] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0 g of primary antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0 g of secondary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 1.2 g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), 2.0 g of hindered amine light stabilizer 944 (Beijing Tiangang Additives Co., Ltd.), and 4 g of composite additives with a mass ratio of HS-765 / powdered styrene-butadiene rubber of 1:5 (i.e., the composite additives prepared in Preparation Example 1) were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0079] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0080] Blown plastic film: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0081] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0082] Example 3:
[0083] The linear low-density polyethylene resin composition was prepared using the following method:
[0084] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0 g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0 g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 1.2 g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), 2.0 g of hindered amine light stabilizer 944 (Beijing Tiangang Additives Co., Ltd.), and 4 g of composite additive (i.e., the composite additive prepared in Preparation Example 1) with a mass ratio of HS-765 / powdered styrene-butadiene rubber of 1:5, and 1.4 g of nucleating agent HPN20E were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0085] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0086] Blown plastic film: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0087] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0088] Example 4:
[0089] The linear low-density polyethylene resin composition was prepared using the following method:
[0090] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0 g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0 g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 1.2 g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), and 6 g of composite additive (i.e., the composite additive prepared in Preparation Example 2) with a weight ratio of HS508 to ethylene-ethyl acetate rubber of 1:10 were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0091] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0092] Blown plastic film: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0093] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0094] Example 5:
[0095] The linear low-density polyethylene resin composition was prepared using the following method:
[0096] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0 g of the following were added: 1.0 g of primary antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.2 g of secondary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 2.0 g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), 6 g of a composite additive (i.e., the composite additive prepared in Preparation Example 2) with a weight ratio of HS508 to ethylene-ethyl acetate rubber of 1:10, and 2 g of light stabilizer (Beijing Tiangang Additives Co., Ltd. HS-625). After being evenly dispersed in a high-speed mixer, the mixture was melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0097] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0098] Blown plastic film: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0099] Test the longitudinal / transverse tensile load and nominal strain at break of the mulch film before and after aging.
[0100] Example 6:
[0101] The linear low-density polyethylene resin composition was prepared using the following method:
[0102] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 32000.0g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 2.0g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), 6g of composite additive of HS508 and ethylene-ethyl acetate rubber in a weight ratio of 1:10 (i.e., the composite additive prepared in Preparation Example 2), 2g of HS-625 light stabilizer from Beijing Tiangang Additives Co., Ltd., and 1.4g of Milliken nucleating agent HPN20E were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0103] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0104] Blown plastic film: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0105] Test the longitudinal / transverse tensile load and nominal strain at break of the mulch film before and after aging.
[0106] Comparative Example 1:
[0107] The linear low-density polyethylene resin composition was prepared using the following method:
[0108] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 1.2g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), and 6.0g of hindered amine light stabilizer 944 (Beijing Tiangang Additives Co., Ltd.) were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0109] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0110] Then, blown plastic film is produced: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0111] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0112] Comparative Example 2:
[0113] The linear low-density polyethylene resin composition was prepared using the following method:
[0114] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0 g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0 g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), and 2.0 g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh) were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0115] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0116] Then, blown plastic film is produced: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0117] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0118] Comparative Example 3
[0119] The linear low-density polyethylene resin composition was prepared using the following method:
[0120] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min, density: 0.918 g / cm³). 3 2000.0g of main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.), 1.0g of auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.), 1.2g of talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh), 2.0g of hindered amine light stabilizer 625 (Beijing Tiangang Additives Co., Ltd.), and 1.4g of nucleating agent (Melicon HPN-20E) were dispersed evenly in a high-speed mixer, and then melt-blended and granulated by a twin-screw extruder to obtain a linear low-density polyethylene resin composition.
[0121] The initial mixing and melt blending processes of the materials, as well as the specific processes for blowing the mulch film, are the same as in Example 1.
[0122] Then, blown plastic film is produced: nominal thickness 10 micrometers, blow-up ratio 2.9.
[0123] Test the longitudinal and transverse tensile loads and nominal strain at break of the plastic film before and after aging.
[0124] Comparative Example 4
[0125] The linear low-density polyethylene resin composition and blown mulch film were prepared using the same method as in Example 1. The difference was that the composite additives prepared in Example 1 were not added in this comparative example, but 1g of HS-765 was used instead of the composite additives.
[0126] Verification showed that the aging tensile load and nominal strain at break of the obtained mulch film were much worse than those of Comparative Example 1. This may be because only liquid light stabilizer was added, which is easy to migrate in the resin matrix and cannot play an anti-aging role. Under the action of ultraviolet light and heat, the weather resistance of the mulch film will be poor.
[0127] Comparative Example 5
[0128] The linear low-density polyethylene resin composition and blown mulch film were prepared using the same method as in Example 1. The difference was that the composite additives prepared in Example 1 were not added in this comparative example, but 5g of powdered styrene-butadiene rubber was used instead of the composite additives.
[0129] Verification showed that the aging tensile load and nominal strain at break of the obtained mulch film were much worse than those of Comparative Example 1. This is because the addition of powdered styrene-butadiene rubber, under ultraviolet, light, and heat aging conditions, cannot absorb the generated free radicals and does not contribute to weather resistance. The addition of cross-linked rubber particles alone does not improve the weather resistance of the mulch film.
[0130] Comparative Example 6
[0131] The linear low-density polyethylene resin composition and blown mulch film were prepared using the same method as in Example 1. The difference was that the composite additives prepared in Example 1 were not added; instead, 5g of powdered styrene-butadiene rubber + 1g of HS-765 were used to replace the composite additives. The specific method was as follows:
[0132] Weigh the LLDPE resin powder (Chemical Branch of Zhongtian Hechuang Energy Co., Ltd., melt index: 1.0 g / 10 min (test conditions: 190±5℃, load 2.16 kg), density: 0.918 g / cm³). 3 2000.0g, main antioxidant 1010 (Yingkou Fengguang New Materials Co., Ltd.) 1.0g, auxiliary antioxidant 168 (Yingkou Fengguang New Materials Co., Ltd.) 1.2g, talc powder (Hebei Jianhui Minerals Co., Ltd., 3000 mesh) 2.0g, HS-765 1g, powdered styrene-butadiene rubber mass ratio 5g, by twin-screw melt blending and granulation.
[0133] Verification showed that the aging mechanical properties of the resulting mulch film, including transverse and longitudinal tensile loads and nominal strain at break, retained only about 50%. This is because HS765, as a medium-molecular-weight hindered amine light stabilizer, rapidly migrates to the film surface during processing and use, proving effective in the short term but exhibiting poor long-term weather resistance. Therefore, the manufacturer recommends its use in thicker products (greater than 3mm).
[0134] Table 1
[0135]
[0136]
[0137] Table 2. Tests on the physical and mechanical properties of plastic film before and after artificial climate aging.
[0138]
[0139] The data above shows that, before modification, Comparative Example 1, which only added solid light stabilizer (i.e., high molecular weight light stabilizer) 944, had a transverse tensile load of about 1.7 N before and after aging, which is only slightly higher than the Xinjiang mulch film standard requirement, and is not conducive to the recycling of mulch film.
[0140] Before modification, Comparative Example 2, which did not add light stabilizer, had a transverse tensile load of less than 1.6N after aging, and a nominal transverse fracture strain of only 55%, which could not meet the national standard requirements for mulch film.
[0141] Before modification, Comparative Example 3, which added solid light stabilizer 944 and nucleating agent, showed a significant increase in nominal strain at break before and after aging, but its transverse tensile load after aging was only about 1.8 N, which was a limited improvement and still not conducive to the recycling of the mulch film.
[0142] In this invention, after modification with a composite additive containing liquid light stabilizer HS-765 and / or powdered styrene-butadiene rubber (e.g., compared to Comparative Example 2 in Example 1, compared to Comparative Example 1 in Example 2, and compared to Comparative Example 3 in Example 3), the longitudinal / transverse tensile load and nominal strain at break of Examples 1-3 before and after aging were significantly improved. The longitudinal and transverse tensile loads of the aged samples were both higher than 2N, and the nominal strain at break in both longitudinal and transverse tensile properties were both higher than 250%. The improved mechanical properties are beneficial for maintaining the performance of the mulch film during mulching and can significantly improve the recycling rate of the mulch film after use.
[0143] After modification with a composite additive made by compounding liquid light stabilizer HS-508 with ethylene-ethyl acetate rubber (for example, compared with Comparative Example 2 in Example 4, compared with Comparative Example 1 in Example 5, and compared with Comparative Example 3 in Example 6), the longitudinal / transverse tensile load and nominal strain at break of Examples 4-6 before and after aging were significantly improved. The longitudinal and transverse tensile loads of the aged samples were both higher than 2N, and the nominal strain at break in both the longitudinal and transverse directions were both higher than 250%, which can significantly improve the recycling rate of the mulch film after use.
[0144] Comparing Comparative Examples 4, 5, and 6 with Example 1, it is evident that adding liquid light stabilizer or crosslinked rubber particles alone, or adding liquid light stabilizer and crosslinked rubber particles as individual raw materials to the composition without preparing a composite additive, significantly reduces the longitudinal / transverse tensile load and nominal longitudinal / transverse breaking strain of the resulting linear low-density polyethylene resin composition after aging, failing to meet the mechanical recycling requirements of the mulch film. Therefore, the linear low-density polyethylene (LLDPE) resin composition of the present invention, containing a composite additive of liquid light stabilizer and crosslinked rubber particles, exhibits a synergistic effect, resulting in unexpected technical advantages.
[0145] By comparing Example 2 with Example 1, and Example 5 with Example 4, it can be seen that the linear low-density polyethylene resin composition of the present invention preferably adds a solid light stabilizer on the basis of adding composite additives. The linear low-density polyethylene resin composition under the above-mentioned preferred formulation has higher longitudinal / transverse tensile load and higher transverse and longitudinal nominal strain at break before or after aging, and further achieves unexpected technical effects.
[0146] By comparing Example 3 with Examples 1 and 2, and by comparing Example 6 with Examples 4 and 5, it can be further seen that the present invention further preferably adds a solid light stabilizer and a nucleating agent on the basis of adding composite additives. The linear low-density polyethylene resin composition under this more preferred formulation has higher longitudinal / transverse tensile load and higher transverse and longitudinal nominal strain at break before or after aging, and further achieves unexpected technical effects.
[0147] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
[0148] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.
[0149] When this specification uses the prefixes “known to those skilled in the art,” “prior art,” or similar terms to derive materials, substances, methods, steps, apparatus, or components, the objects derived from such prefixes cover those commonly used in the art at the time of this application, but also include those that are not currently commonly used but will become generally recognized in the art as suitable for similar purposes.
[0150] The endpoints and any values of the ranges disclosed in this application are not limited to the precise ranges or values; such ranges or values should be understood to include values close to them. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In principle, various technical solutions can be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.
[0151] In the context of this specification, except where expressly stated otherwise, any matters or issues not mentioned shall apply directly to those known in the art without any modification.
[0152] Furthermore, any implementation described herein can be freely combined with one or more other implementations described herein, and the resulting technical solutions or technical ideas shall be regarded as part of the original disclosure or original record of the present invention, and should not be regarded as new content not disclosed or anticipated herein, unless those skilled in the art consider the combination to be obviously unreasonable.
Claims
1. A linear low-density polyethylene resin composition comprising LLDPE resin, an antioxidant, an opening agent, a compounding agent, an optional nucleating agent, and an optional solid hindered amine light stabilizer, wherein the compounding agent comprises a liquid light stabilizer and crosslinked rubber particles, the liquid light stabilizer being loaded on the surface of the crosslinked rubber particles.
2. The linear low-density polyethylene resin composition according to claim 1, characterized in that: The crosslinked rubber particles are selected from at least one of the following rubber particles having a crosslinked structure: styrene-butadiene rubber particles, carboxylated styrene-butadiene rubber particles, natural rubber particles, acrylate rubber particles, ethylene-vinyl acetate copolymer particles, isoprene rubber particles, and butadiene acrylate particles; preferably selected from at least one of styrene-butadiene rubber particles, carboxylated styrene-butadiene rubber particles, and ethylene-vinyl acetate copolymer particles; and / or, The gel content in the cross-linked rubber particles is 60 wt% or higher; and / or; The cross-linked rubber particles are secondary particles composed of primary particles, wherein the average particle size of the primary particles is 0.1-1 micrometer, preferably 0.1-0.5 micrometers, and the average particle size of the secondary particles is 10-60 micrometers, preferably 20-40 micrometers; and / or, The liquid light stabilizer is a liquid hindered amine light stabilizer.
3. The linear low-density polyethylene resin composition according to claim 1, characterized in that: The composite additive is a composite additive formed by loading a liquid light stabilizer onto the surface of spherical or nearly spherical cross-linked rubber particles; preferably, The preparation method of the composite additive includes: The irradiated crosslinked rubber latex is mixed with a liquid light stabilizer and then spray-dried to prepare a powdered composite additive; more preferably, The weight ratio of the liquid light stabilizer to the rubber latex, based on solid content, is (5-15):100; and / or, The rubber latex raw materials include at least one of the following: styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, natural rubber latex, acrylate rubber latex, ethylene-vinyl acetate copolymer latex, isoprene rubber latex, and acrylic-butadiene latex, preferably styrene-butadiene rubber latex, carboxylated styrene-butadiene rubber latex, and ethylene-vinyl acetate copolymer latex.
4. The linear low-density polyethylene resin composition according to claim 1, characterized in that: The LLDPE resin is copolymerized from ethylene and an α-olefin, wherein the α-olefin is preferably selected from at least one of butene-1, hexene-1, and octene-1; preferably... Under conditions of 190±5℃ and a load of 2.16kg, the melt flow rate of the LLDPE resin is ≤10g / 10min, preferably ≤4g / 10min, more preferably ≤2.5g / 10min; and / or, The nucleating agent is selected from at least one of organic nucleating agents and inorganic nucleating agents, preferably from at least one of organic carboxylic acid nucleating agents, organic carboxylate nucleating agents, and organic phosphate nucleating agents, and more preferably from at least one of nucleating agent NA11, nucleating agent NA21, and nucleating agent 20E; and / or, The solid hindered amine light stabilizer is selected from at least one of light stabilizer 770, light stabilizer 944, light stabilizer 622, and light stabilizer 3346.
5. The linear low-density polyethylene resin composition according to claim 1, characterized in that: The antioxidants include primary antioxidants and secondary antioxidants; Preferably, the primary antioxidant is a hindered phenolic antioxidant, and is preferably selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1330, antioxidant 3114, antioxidant 1135, and antioxidant 1790; And / or, preferably, the auxiliary antioxidant is selected from at least one of phosphite antioxidants and thioester antioxidants, more preferably from at least one of phosphite antioxidants; more preferably, The phosphite antioxidant is selected from at least one of antioxidant TNPP, antioxidant 168, antioxidant 618, antioxidant 626, antioxidant PEP-36, tetrakis(2,4-di-tert-butyloctakoxy-4,4'-biphenyl) phosphate, and antioxidant 398; and / or, preferably, Based on parts by weight, relative to 1000 parts of LLDPE resin, the content of hindered phenolic antioxidant is 0.3-3 parts, preferably 0.3-2 parts, more preferably 0.5-1 parts; the content of phosphite antioxidant is 0.3-3 parts, preferably 0.3-2 parts.
6. The linear low-density polyethylene resin composition according to claim 1, characterized in that: Based on parts by weight, the opening agent content is 1-10 parts, preferably 1-5 parts, relative to 1000 parts of LLDPE resin; and / or, The opening agent is selected from at least one of inorganic opening agents and organic opening agents; Preferably, the inorganic opening agent is selected from at least one of talc, diatomaceous earth, and silica; and / or, Preferably, the organic opening agent is selected from at least one of oleamide and erucamide.
7. The linear low-density polyethylene resin composition according to any one of claims 1-6, characterized in that: Based on parts by weight, relative to 1000 parts of LLDPE resin, the linear low-density polyethylene resin composition contains 0.3-2 parts of composite additives; 0-2 parts of solid hindered amine light stabilizer, preferably 0.3-2 parts; 0-1.5 parts of nucleating agent, preferably 0.3-1.5 parts, more preferably 0.5-1.2 parts; and / or, The weight ratio of the liquid light stabilizer to the crosslinked rubber particles in the composite additive is (5-15):
100.
8. A method for preparing a linear low-density polyethylene resin composition according to any one of claims 1-7, comprising melt-blending raw materials including the LLDPE resin, antioxidant, opening agent, composite additive, optional nucleating agent, and optional solid hindered amine light stabilizer to obtain the linear low-density polyethylene resin composition; preferably, comprising the following steps: Step 1: Premix the raw materials including the LLDPE resin, antioxidant, opening agent, composite additive, optional nucleating agent, and optional solid hindered amine light stabilizer; or, prepare an additive composition from the additive raw materials including the antioxidant, opening agent, composite additive, optional nucleating agent, and optional solid hindered amine light stabilizer, and then premix the additive composition with the LLDPE resin. Step 2: The premixed mixture obtained in Step 1 is melt-blended to obtain the linear low-density polyethylene resin composition.
9. A polyethylene film, wherein the polyethylene film is made of the linear low-density polyethylene resin composition according to any one of claims 1-7 or the linear low-density polyethylene resin composition prepared by the preparation method according to claim 8; Preferably, the polyethylene film is obtained by blow molding, and more preferably, the blow-up ratio is >2.
5.
10. A method for preparing a polyethylene film according to claim 9, comprising the step of blow molding a linear low-density polyethylene resin composition according to any one of claims 1-7 or a linear low-density polyethylene resin composition prepared by the method according to claim 8, preferably with a blow-up ratio > 2.
5.
11. The application of a linear low-density polyethylene resin composition according to any one of claims 1-7, or a linear low-density polyethylene resin composition prepared by the preparation method according to claim 8, or a polyethylene film according to claim 9, or a polyethylene film prepared by the preparation method according to claim 10, in mulch film.
